PENGARUH LINGKUNGAN KELUARGA, TEMAN SEBAYA DAN SMARTPHONE TERHADAP MOTIVASI BELAJAR SISWA / THE INFLUENCE OF FAMILY, PEER AND SMARTPHONE ENVIRONMENT ON STUDENTS' LEARNING MOTIVATION - Salamah, Umi; Halimatus Sa’diyah (STAI Ma'had Aly Al-Hikam Malang, 2024)
This research aims to explain the influence of the family environment on student learning motivation, the influence of peers on student learning motivation, and the influence of smartphones on student learning motivation, the influence of the family environment, peers and smartphones together on student learning motivation. The approach in this research uses a quantitative approach. The research population was all Al-Faqih Pakis students in Malang Regency, totaling 110 students. Meanwhile, the sampling technique used random sampling and a sample of 86 students was obtained. Data collection techniques using questionnaires and documentation. The data analysis technique uses multiple linear regression analysis, T test, F test and coefficient of determination. Based on the analysis of the partial test (T test) and simultaneous test (F test), it can be concluded that the family environment variable and peer variables have a significant effect on the learning motivation variable, while the smartphone variable has less influence on the learning motivation variable. And simultaneously, family environment variables, peers and smartphones have an influence on learning motivation variables.